Simple, accurate and user-friendly differential constitutive model for the rheology of entangled polymer melts and solutions from nonequilibrium thermodynamics - Stephanou, Pavlos S.; Tsimouri, Ioanna Ch; Mavrantzas, Vlasis G. (My University, 2020)
In a recent reformulation of the Marrucci-Ianniruberto constitutive equation for the rheology of entangled polymer melts in the context of nonequilibrium thermodynamics, rather large values of the convective constraint release parameter βccr had to be used in order for the model not to violate the second law of thermodynamics. In this work, we present an appropriate modification of the model, which avoids the splitting of the evolution equation for the conformation tensor into an orientation and a stretching part. Then, thermodynamic admissibility simply dictates that βccr ≥ 0, thus allowing for more realistic values of βccr to be chosen. Moreover, and in view of recent experimental evidence for a transient stress undershoot (following the overshoot) at high shear rates, whose origin may be traced back to molecular tumbling, we have incorporated additional terms into the model accounting, at least in an approximate way, for non-affine deformation through a slip parameter. Use of the new model to describe available experimental data for the transient and steady-state shear and elongational rheology of entangled polystyrene melts and concentrated solutions shows close agreement. Overall, the modified model proposed here combines simplicity with accuracy, which renders it an excellent choice for managing complex viscoelastic fluid flows in large-scale numerical calculations.
Keywords: Concentrated polymer solutions; Entangled polymermelts; Nonequilibriumthermodynamics; Polymer tumbling; Transient shear viscosity undershoot